Uniform Ni-rich LiNi0.6Co0.2Mn0.2O2 Porous Microspheres: Facile Designed Synthesis and Their Improved Electrochemical Performance. (10th February 2016) - Zheng, Zhuo; Guo, Xiao-Dong; Chou, Shu-Lei; Hua, Wei-Bo; Liu, Hua-Kun; Dou, Shi Xue; Yang, Xiu-Shan
Abstract: A facile two-step synthetic route, i.e., combining the carbonate co-precipitation method and impregnation method, to prepare uniform porous Ni-rich LiNi0.6 Co0.2 Mn0.2 O2 microsphere with an average diameter of ∼3 μm and BET specific surface area of 13.4 m 2  g −1 is proposed for the first time. The XRD and TEM results confirm that the porous microspheres LiNi0.6 Co0.2 Mn0.2 O2 material has a well-ordered α-NaFeO2 structure with stable in-plane [ 3 × 3 ]R30° ordering in the transition-metal layers. The exquisite morphology and ideal structure endow this nanocrystal-assembled porous LiNi0.6 Co0.2 Mn0.2 O2 microspheres enhanced electrochemical performance such as high capacity, good cycling stability and excellent rate capability. Specifically, the as-prepared porous LiNi0.6 Co0.2 Mn0.2 O2 cathode delivers a high discharge capacity of 79 mAh g −1 even at the ultrahigh rate 50C (10 A g −1 ), and 138 mAh g −1 at 1C after 100 cycles with an excellent cycle life. Additionally, the fast-charging test results are indicative of the fact that this cathode has sufficiently stable structure, because it can still deliver a discharge capacity higher than 123 mAh g −1 after 100 cycles with capacity retention of 90.1% at 5C charge and 1C discharge. The cyclic voltammetry (CV) and electrochemical impedance spectra (EIS) results demonstrate that the porous LiNi0.6 Co0.2 Mn0.2 O2 cathode has a higher apparent lithium ion diffusion coefficient (insertion/extraction process are 8.67 × 10 −8 and 3.78 × 10 −8  cm 2  s −1, respectively) and lower activation energy (29.3 KJ mol −1 ). Our results indicate that this preparation strategy may be facile and versatile for synthesis other high-capacity anode/cathode materials.